Cinematic metaphor in perspective reflections on a transdisciplinary framework - Greifenstein, Sarah; Horst, Dorothea; Kappelhoff, Hermann; Müller, Cornelia, 1960-; Scherer, Thomas (Film scholar); Schmitt, Christina (Cinepoetics ;, 2018)
Over centuries, scholars have explored how metaphor contributes to thought, language, culture. This collection of essays reflects on Müller, Kappelhoff, and colleagues' transdisciplinary (film studies and linguistics) approach formulated in "Cinematic Metaphor: Experience - Affectivity - Temporality". The key concept of cinematic metaphor opens up reflections on metaphor as a form of embodied meaning-making in human life across disciplines. The book documents collaborative work, reflecting intense, sometimes controversial, discussions across disciplinary boundaries. In this edited volume, renowned authors explore how exposure to the framework of Cinematic Metaphor inspires their views of metaphor in film and of metaphor theory and analysis more generally. Contributions include explorations from the point of view of applied linguistics (Lynne Cameron), cognitive linguistics (Alan Cienki), media studies (Kathrin Fahlenbrach), media history (Michael Wedel), philosophy (Anne Eusterschulte), and psychology (Raymond W. Gibbs, Jr.).